DETEKSI WAJAH MENGGUNAKAN METODE NEURAL NETWORK BERBASIS ANDROID - Firdiyan Syah (Universitas PGRI Yogyakarta, 2019)
The development of technology that continues to grow, especially in the field of face detection makes innovation continue to be developed. This development is in accordance with the needs that are changing rapidly and then the technology answers these challenges with an algorithm designed. One of them is the parking area of ​​the University of PGRI Yogyakarta, which now has more than 200 employees but there is very limited parking space, so if it is not set up, the parking area of ​​the employee will be very full and if it is not regulated, only employees may enter insufficient parking area. Budget constraints and humanist factors make choosing technology wise. So that employee parking areas can be monitored only employees can enter and then parking capacity can be monitored, then Android-based face detection technology is chosen. Only faces that have entered the database can enter the employee parking area. The method for face detection uses Neural Network. With face detection when entering a parking area, a special employee parking area can be used comfortably and the capacity can be monitored properly.